Prevalence and burden of HBV–HIV co-morbidity: a global systematic review and meta-analysis - Dagnaw, Mequanente; Muche, Achenef Asmamaw; Geremew, Bisrat Misganaw; Gezie, Lemma Derseh (Frontiers in Public Health, 2025)
IntroductionHepatitis B is a serious liver infection caused by the hepatitis B virus (HBV). Because of the shared modes of transmission, co-infections of HBV are common among people living with Human Immunodeficiency Virus (HIV) infection. While the use of antiretroviral therapy (ART) has significantly improved the life expectancy of HIV patients, hepatitis viral co-infections have become increasingly important. Particularly, HBV infection remains under-diagnosed and under-reported, despite its highly infectious nature. Therefore, this review was aimed at understanding the burden of hepatitis B disease among adults living with HIV receiving ART.MethodsUsing pertinent search terms, all research found in Google Scholar, HINARI, EMBAS, Scopus, and PubMed was located. Data were extracted following the evaluation of the evidence using the Joanna Briggs Institute’s cross-sectional and cohort study methodologies.ResultA total of 18 groups involving 71,411 adults with HBV–HIV were selected for the study. Of those, 10.21% with 95% CI (5.06, 15.36) and 11.05% with 95% CI (2.78, 19.32) of HBV–HIV adults worldwide had an overall prevalence of HBV, with an I2 value of 0.0% (p-value = 0.729) and an I2 value of 0.0% (p-value = 0.818) from cross-sectional and cohort studies, respectively.ConclusionThe global prevalence of people living with HBV–HIV is high, which poses a serious risk to public health. The review can clearly show the current pooled prevalence of HIV–HBV in the world, which may be helpful for policymakers because a large number of recent studies were included in it. Thus, it is strongly advised to broaden the current preventive and control program’s purview and implement new, sensitive screening, testing, and treatment techniques. To raise community awareness, it would also be preferable to revamp the current prevention and control program and establish target-specific task forces at various health facility levels.